REVISITING ORAL IMPLANTOLOGY: NAVIGATING THE COMPLEXITIES OF CONGENITAL AND DEGENERATIVE BONE DISORDERS - KHETARPAL, SHALEEN; RATRE, MADHU SINGH; PATLE, NEHA; VERMA, MANISH; BANSAL, RESHAMA; MP, ALFAS RASI (South Eastern European Journal of Public Health, 2024)
The placement of implants in patients with congenital and degenerative bone disorders presents significant challenges due to compromised bone strength and volume. These conditions often result in fragile, misaligned, or insufficient bone structures that complicate traditional implant techniques and outcomes. Diseases such as osteogenesis imperfecta, rheumatoid arthritis, Paget's disease, and other systemic skeletal conditions exacerbate these difficulties. This review explores various strategies to improve implant outcomes, including bone grafting, osteoinductive agents, advanced implant designs, and the use of 3D imaging and computer-assisted design technologies to enhance pre-surgical planning and address anatomical limitations. It emphasizes the need for a multidisciplinary approach, involving dental, medical, and surgical teams, to ensure successful treatment outcomes. Moreover, emerging biological therapies, especially stem cell-based strategies, hold great promise for promoting bone regeneration and enhancing implant integration in individuals with fragile bone structures. The review also delves into the underlying mechanisms of these disorders, their effects on bone remodelling, and the altered healing processes that influence implant success.